Canopy Herbivory and Insect Herbivore Diversity in a Dry Forest-Savanna Transition in Brazil - Neves, Frederico S; Araújo, Lucimar S; Espírito-Santo, Mário M; Fagundes, Marcílio; Fernandes, G. Wilson; Sanchez-Azofeifa, G. Arturo; Quesada, Mauricio (Biotropica, 2010)
This study aimed to compare canopy herbivore diversity and resultant insect damage to vegetation in two distinct and adjacent ecosystems, specifically a dry forest ecosystem and a cerrado (savanna) ecosystem that occur together in an abrupt transition zone in southeastern Brazil. In the dry forest, the canopy was reached using a single rope climbing technique, whereas the shorter canopy of the cerrado was assessed using a 7 m ladder. Insect specimens were collected by beating the foliage, and 20 representative leaves were collected to calculate the specific leaf mass (SLM) and leaf area loss through herbivory. Also, we collected ten soil samples from each habitat to determine soil nutrient content. We sampled 118 herbivorous insects from ten families, mostly in dry forest trees (96 individuals belonging to 31 species). A higher abundance of chewing and sap-sucking insects were observed in dry forest trees than in cerrado trees. The same pattern was observed for the richness of chewers, with a higher degree of diversity of chewers found in dry forest trees than in cerrado trees. Herbivorous insects were not affected by SLM regardless of guild and habitat. However, we observed a negative correlation between the herbivory rate and the specific leaf mass (SLM). The cerrado trees showed a higher SLM and lower herbivory rates than trees occurring in the dry forest. These results suggest that herbivory rates in the transition dry forest-cerrado may be driven by soil nutrient content, which is thought to influence leaf sclerophylly. Abstract in Portuguese is available at http://www.blackwell-synergy.com/loi/btp.